Health risks associated with municipal waste combustion on the example of Laskowa commune (Southern Poland). Issue 8 (17th November 2017) - Kicińska, Alicja; Mamak, Magdalena
ABSTRACT: This study presents the results of an analysis of combustion waste, namely fly ashes produced from the burning of solid fuels mixed with municipal waste. Heavy metal concentrations in the fly ashes examined fell within the following ranges (mg/kg): Cd 0.39–0.79, Cr 13.48–58.51, Ni 17.01–49.37 and Pb 14.95–59.74. As this type of waste does not exceed the limit values of pollutants for organic and organic-mineral fertilisers, it is often discarded on agricultural land or dumped in illegal landfills. Fine particles of fly ashes travel considerable distances and pose a risk to human health as they stick to people's hands during field works. The mean hazard quotient (HQ) values for non-carcinogenic forms of the elements analysed were 1.06E+00 for children and 1.47E-01 for adults. A HQ>1 indicates the probability of adverse health effects. The study has shown that the dominant exposure pathway was ingestion, which accounted for approx. 91% of total health risk, while the respective percentages for other pathways were less than 9% for dermal contact and 0.05% for inhalation. The highest health risk in the ingestion exposure pathway was observed for Cr (HQing = 4.50E-01 for children, HQing = 5.23E-02 for adults) and Pb (HQing = 4.31E-01 for children, HQing = 5.01E-02 for adults). Health risk associated with the presence of Ni and Cd in the material analysed was markedly lower. For carcinogenic forms, the Risk index was established at 6.13E-08 for children and 2.13E-07 for adults. As the exposure limit (10E-5) was not exceeded, the conditions in the area studied should be considered satisfactory.